Intrapartum ultrasound monitoring of malposition and malrotation during labor neuraxial analgesia: maternal outcomes. (1st November 2020) - Malvasi, Antonio; Raimondo, Pasquale; Beck, Renata; Tinelli, Andrea; Kuczkowski, Krzysztof Marek
Abstract: Objective: This study analyzes the important role of ultrasonography (IUS) related to the maternal outcomes in women with fetal persistent occiput posterior position (POPP) and asynclitism (A) in labor neuraxial analgesia (LNA). Study design: Prospective assessment of 148 primiparous women diagnosed with the prolonged second stage of labor. Transabdominal and transperineal IUS were used to detect fetal head position and to evaluate the angle of progression (AOP) and pubic arch angle (PAA). Statistical data about maternal aspects, modalities of delivery and maternal outcomes were observed. Results: In all parturients included in the study, the operative delivery rate was 73%. In patients delivered via cesarean section, the PAA was ≤ of 96.5°. There was statistical correlation between doses of LNA and Apgar score at first minute (r0.8). Conclusions: There is a greater frequency of Fetal POPP and asynclitism related with maternal complications. The results of our study confirmed the importance of determination of angle of progression (AoP) and PAA in the prolonged second stage of labor. Unfavorable AoP and PAA, in presence of POPP and A, are related with high percentage of operative delivery. If the prolonged labor and delivery in these patients exceed time limit proposed by American College of Obstetricians and Gynecologists guidelines, it may be viewed as a possible malpractice. In cases of POPP with asynclitism, in the second stage of labor detected by IUS it is advisable to discontinue the anesthetic drugs administration in LNA; because the labor pain is related to the dystocia, an operative delivery is necessary to avoid maternal and fetal complications.